Grasp Patterns and Anti-Patterns: an Object Oriented Approach from Logic Programming (2019)
This article presents a teaching strategy for introducing the use of patterns GRASP (General Responsibility Assignment Software Patterns) and the disuse of anti-design patterns in the course  “fundamentals object-oriented programming”, where problems are solved according to four phases: identification of requirements, design class diagram, specification of responsibilities and pseudocode writing.